Development Status and Trend of IPTV and OTT TV - Li Jiang; Zhuxiang Deng (Dianxin kexue)
The definition of IPTV and OTT TV was described as well as development status，and the differences both in the business model and technology were also analyzed.From the user’s point of view，the main form of television in the future，and a detailed analysis of the end trends of IPTV and OTT TV business were depicted.